An Analysis Of Students’ Sentences With Inverted Subjects And Verbs Error Found In Tmi’s Toefl Preparation Class - Agung Pranoto Kadiatmaja (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2021)
The research is to find out the types of error analysis in students’ sentences and the most dominant types of error analysis in students’ sentences. This research uses qualitative method to look into errors in the second language acquisition and to collect empirical data. This method is applied to get the accurate data collection. The object of the research is students’ practice randomly taken from twelve advanced students of TOEFL Preparation Class – The Mushlih Institute (TMI) Surabaya. In acquiring the result of this error analysis, surface strategy taxonomy is applied to investigate more details. It is limited on the students’ sentences with inverted subjects and verbs error in their practice consisting of four error types. In summary, the types of sentences with inverted subjects and verbs errors produced by the students are (1) omission appearing 49 times or 79,03% of all, (2) addition appearing 9 times or 14,52% of all, (3) misordering appearing 3 times or 4,84% of all, and (4) misformation appearing a time or 1,61% of all. According to the research findings, the most dominant type of sentences with inverted subjects and verbs error is omission.